Embolic stroke of undetermined source and patent foramen ovale closure: Practice insights from meta‐analysis?. Issue 6 (26th November 2018) - Chatterjee, Arka; Hillegass, William B.
Key Points: Closure of patent foramen ovale (PFO) in embolic stroke of undetermined source (ESUS) reduces recurrent stroke compared with antiplatelet therapy in select patients but increases risk of atrial fibrillation. Device closure is an attractive option for young patients with an anatomically higher risk PFO and imaging proven ESUS. Benefit of PFO closure in ESUS compared with oral anticoagulation remains undefined.